STRENGTHENING PEDAGOGICAL COMPETENCE OF TEACHERS OF ULUMUL QUR'AN PIDIE JAYA JUNIOR HIGH SCHOOL AND ITS IMPLICATIONS - Maulidin, Maulidin; Abdullah, Nazaruddin; Saifuddin, Saifuddin (MSJ : Majority Science Journal, 2025)
This study aims to analyze the strengthening of teachers' pedagogical competence at SMP Ulumul Qur'an Pidie Jaya, focusing on the forms of strengthening, its implications for learning, and the supporting and inhibiting factors. The research employs a qualitative approach with a case study method through interviews, observations, and documentation. The findings reveal that pedagogical competence is strengthened through regular class supervision, internal and online training, and participation in learning communities. These enhance teachers' understanding of student characteristics, mastery of learning theories, and the ability to design and implement effective learning tailored to students' needs. As a result, learning becomes more engaging and efficient, contributing to both academic and non-academic achievements, as reflected in improved student performance. The main supporting factors include the principal's support through supervision and training, as well as active teacher involvement in learning communities. However, challenges arise from limited time, facilities, technological resources, and difficulties in adapting teaching methods to the diverse characteristics of students.